(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article provides a clear overview of the skills and directions for learning a foreign language and obtaining a language proficiency certificate. It is explained how much we need foreign languages and how important their role is in our lives. This article analyzes the concept, essence, characteristics of the methods and methods used in teaching foreign languages, and methods of teaching the methodology.